HUBUNGAN LETAK LESI HEMISFER SEREBRAL DAN DERAJAT KLINIS KECEMASAN PADA PENDERITA STROKE ISKEMIK - Yelly Marliana Patu,* Audry Devisanty Wuysang,* Nadra Maricar* (NEURONA, 2018)
INTRODUCTION STROKE IS THE LEADING CAUSE OF DISABILITY AND THE THIRD CAUSE OF DEATH IN THE WORLD THE LESION IN THE RIGHT HEMISPHERE IS MOST OFTEN ASSOCIATED WITH ANXIETY